The Main Directions of Supply Chain Management Development of Territorial Branding in Russia in Modern Conditions - Boris Mojshevich Eidelman; Oleg Aleksandrovich Bunakov; Liliya Raisovna Fakhrutdinova (International Journal of Supply Chain Management, 2019)
Abstract- In article the most important directions of development of territorial branding in Russia are considered based on the supply chain management. Importance and relevance of consideration of the matter taking into account strengthening of competition between regions and need of increase in their competitiveness is shown. Author's definitions of a territorial brand and territorial branding are given. Classification of the Russian territorial brands on the basis of population, living in the respective territory, in the city or the rural settlement was carried out. Authors give a large number of the illustrations opening the maintenance of territorial brands and disclose the main ideas which are been the basis for their designing. In conclusion of article the conclusion was drawn that development and advance of territorial brands significantly increases tourist and recreational and investment attractiveness of regions, and, therefore, promotes acceleration of rates of their social and economic development and improvement of quality of life of local population.